Association between cardiorrespiratory fitness and cognitive control: is somatic maturity an important mediator? - Vinícius Muller Reis Weber; Julio Cesar da Costa; Leonardo Alex Volpato; Marcelo Romanzini; Jose Castro-Piñero; Enio Ricardo Vaz Ronque (BMC, 2022)
Abstract Background Recently some articles presented information related to the possible effect of maturity over the cognitive control and cardiorespiratory fitness, however little is known about the real effects of maturity in the relation of these variables. In this sense, the purpose of this study was to examine the potential mediating role of somatic maturity on the association between cardiorespiratory fitness (CRF) and cognitive control. Methods This three-year longitudinal research comprises two data collection groups: a baseline conducted in 2016 with 394 adolescents (aged 11.7 ± 0.6 years) and a follow-up in 2019 with 134 adolescents (aged 14.9 ± 0.7 years). Anthropometry data, 20-m shuttle run test and peak height velocity (PHV) to determine the maximum oxygen uptake (VO2max) and somatic maturity, respectively, were collected at both sampling times. In parallel, the Sociodemographic and cognitive control function variables were included in the follow-up to evaluate the inhibitory control (by the Stroop test) and the visuo-spatial working memory (by the Corsi block-tapping test). Associations between CRF and cognitive functions were computed by multiple linear regression, with mediation as a function of PHV. Results CRF exhibited transversal associations with reaction time in congruent (β = -0.004; p = 0.001) and incongruent (β = -0.005; p = 0.004) stimulus-responses. Meanwhile, the variation in VO2max over the three year-study had a significant impact on the reaction time of congruent (β = -0.006; p = 0.001) and incongruent (β = -0.006; p = 0.012) responses at follow-up. However, PHV did not show a significant association with the cognitive functions, indicating no mediating role. Conclusions Although the associations between CRF and the cognitive functions exhibited great transversal and longitudinal impacts, somatic maturity did not affect the cognitive control functions, associating exclusively with CRF.